1996
DOI: 10.1007/bf00145414
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of diphtheria immunity in the population of Florence, Italy

Abstract: A seroepidemiological study was conducted in 1994 on a representative sample of the population of Florence in order to verify the immunity coverage against diphtheria. Subjects were divided according to sex and age class. Sera from each selected class were at least 1.5/1000 of the residing population. Diphtheria antitoxin was titrated using a quantitative ELISA test. The results show an overall adjusted prevalence of diphtheria immunity (> or = 0.01 IU/ml) equal to 63.7%. Subjects of younger age classes have g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
2
6
0
1
Order By: Relevance
“…The results of the present analyses are also in accord with those of several other studies [2–5,12–14,19,21] with respect to the typical age trend in diphtheria immunity. In individuals who were born before diphtheria vaccination became mandatory, immunity is related to natural infection.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present analyses are also in accord with those of several other studies [2–5,12–14,19,21] with respect to the typical age trend in diphtheria immunity. In individuals who were born before diphtheria vaccination became mandatory, immunity is related to natural infection.…”
Section: Discussionsupporting
confidence: 92%
“…A shortened vaccination schedule (3, 5, 12 months) was introduced in Sweden in 1979 and recent studies attest to the fact that the majority of the Swedish population have only low immunity to diphtheria and the rate of protection for 10 year olds did not exceed 52 % [31,32]. A number of earlier studies from Poland, England and elsewhere also showed inadequate protection rates in adults of 20-50 years [10,33] and 30-60 years [11,27,[34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown by various recent studies in Italy [8][9][10][11], France [12], Spain [13][14][15][16], Germany [17,18] and the United Kingdom [19]. Although the major epidemic in East European countries has been in remission since 1996 [20], more than 7000 cases were reported in 1997 and more than 2500 in 1998 [2].…”
Section: Introductionmentioning
confidence: 88%